Trolls, bots and botnets as a threat to the development of the information society - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
This article is topical as average citizens start actively using social networks, and online and electronic platforms in their lives; and it means that evidence the Fourth Industrial Revolution. Nowadays, Ukraine witnesses the acute problem of trolls, bots and botnets threatening the information society. And in the midst of the threats of radical forces and the armed conflict in eastern Ukraine, the EU has also faced this problem. It is commonly known that information warfare means actions taken to achieve information advantages by attacking information and processes, which are based on the enemy’s information and information systems, and protecting own information and processes, which are based on own information and information systems. Trolling that is used within information networks, social environments and platforms is one of the most widespread types of such a warfare. This article aims at analysing new information threats such as trolls, bots and botnets, and their minimisation and elimination ways. For preventing information abuse and protecting information rights, the Ukrainian national and information security currently requires developing the science-based state policy and strategy in this area; defining the system of national values and vital interests of an individuum, the society and the state; determining external and internal threats to these interests; searching for effective means of ensuring security in all areas; protecting against information threats; and realising rights to reliable information. In addition, the mentioned above witnesses that eliminating similar negative phenomena requires implementing media competence improvement programmes and professional online journalism standards, realising property transparency reforms, resisting to political and financial oligarch concentration on the media market and their influence on mass media policy.